A Forward-Backward Kalman Filter-based STBC MIMOOFDM Receiver. (1st February 2009) - Al-Naffouri Al-Naffouri, T. Y. T. Y.; Quadeer Quadeer, A. A. A. A.
Abstract : Orthogonal frequency division multiplexing (O F D M ) has emerged as a modulation scheme that can achieve high data rates over frequency selective fading channel by efficiently handling multipath effects. This paper proposes receiver design for space-time block codedMIMO     O F D M transmission over frequency selective time-variant channels. Joint channel and data recovery are performed at the receiver by utilizing the expectation-maximization (EM ) algorithm. It makes collective use of the data constraints (pilots, cyclic prefix, the finite alphabet constraint, and space-time block coding) and channel constraints (finite delay spread, frequency and time correlation, and transmit and receive correlation) to implement an effective receiver. The channel estimation part of the receiver boils down to anEM -based forward-backward Kalman filter. A forward-only Kalman filter is also proposed to avoid the latency involved in estimation. Simulation results show that the proposed receiver outperforms other least-squares-based iterative receivers.